Polyethyleneimine‐Based Cryogels Enabling the Selective and Reversible Adsorption of Chlorine - Alejandro Lorente; Johanna S. Sturm; Merlin Kleoff; Fabio Lorenz; Patrick Voßnacker; Olaf Wagner; Rainer Haag; Sebastian Riedel (Advanced Science)
Abstract Herein hyperbranched polyethyleneimine (hPEI) cryogels are reported for the selective and reversible adsorption of elemental chlorine. The cryogels are prepared in an aqueous solution by crosslinking with glutaraldehyde at subzero temperatures. The final macroporous composites bearing ammonium chloride groups are obtained after freeze‐drying. The cryogels CG1[Cl]–CG3[Cl] adsorb chlorine with capacities of 0.22–0.26 g Cl2/g cryogel as an average over three adsorption‐desorption cycles. The adsorption process is based on the reversible and selective halogen bonding of chlorides (Cl−) with chlorine (Cl2) forming the corresponding trichloride ([Cl3]−) species, indicated by Raman spectroscopy. The reversibility of chlorine adsorption is shown by applying heat and vacuum to the loaded cryogel CG1[Cl3] releasing 63% of the adsorbed chlorine within 3 h and 72% within 16 h. The unique ability to selectively adsorb chlorine in the presence of other gases is successfully employed for the selective adsorption of chlorine from a gas mixture, potentially enabling the recycling of chlorine from tail gas streams.